Clinical experience in the use of cefuroxime in gonorrhoea. Issue 6 (December 1978) - Fowler, W; Rahim, G; Brown, J D
Abstract : Cefuroxime, a new antibiotic derived from cephalosporin-C which is very stable in the presence of beta-lactamases produced by Gram-negative organisms, was used to treat 856 male patients and 340 female patients with uncomplicated gonorrhoea. In men the drug was used in three different doses, 1.5 g, 1 g, and 750 mg plus 1 g probenecid; in women 1 g and 750 mg cefuroxime plus 1 g probenecid was used. Cure rates ranged from 94.8% to 99.3%. The antibiotic was well tolerated and was free from side effects. Cefuroxime would be a valuable and efficient substitute for penicillin in the treatment of gonorrhoea due to beta-lactamase-producing strains of gonococci.